Theatrum Monstruosum: El lenguaje de lo difuso en el saber clínico colombiano de finales del siglo XIX y comienzos del XX (2005)
The research presented focuses on the modalities in which the Colombian medical practice of the late nineteenth and early twentieth centuries installs enunciative materials that expose the body perceived in a morbid state. Seeing and saying the deforming